Anti-discoloration solid ceramic block, ceramic aromatherapy block and preparation method thereof

By using coordination chelating agents and adsorbents in the car-mounted ceramic aromatherapy block to treat iron ions in the ceramic aromatherapy block, the problem of discoloration of the ceramic aromatherapy block is solved, and the color stability and aesthetics of the product are improved.

CN119504288APending Publication Date: 2025-02-25GUANGDONG CAR HOUSE INDUSTRIAL DEVELOPMENT HOLDINGS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411703867.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing automotive solid ceramic aromatherapy blocks are prone to discoloration after adsorbing fragrances, which affects the beauty of the product. The handling of similar problems on the market usually ignores the discoloration problem and is believed to not affect the fragrance experience.

Method used

By dissolving the coordination chelating agent into alcohol, soaking the ceramic block containing iron ions for chelation reaction, forming a stable chelation complex, and then using an adsorbent to adsorb trace amounts of iron ions in the ceramic block, thereby preventing the complexation reaction of iron ions with phenols or aldehyde fragrances.

Benefits of technology

It effectively prevents the discoloration of ceramic aromatherapy blocks, improves the color stability and aesthetics of the product, and enhances the competitiveness of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154057140000071
    Figure BDA0005154057140000071
  • Figure BDA0005154057140000072
    Figure BDA0005154057140000072
  • Figure BDA0005154057140000081
    Figure BDA0005154057140000081
Patent Text Reader

Abstract

The invention discloses an anti-discoloration solid ceramic block, a ceramic aromatherapy block and a preparation method thereof, and the preparation method of the anti-discoloration solid ceramic block comprises the following steps: S1, dissolving a coordination chelating agent in alcohol to prepare a coordination chelating agent alcohol solution; s2, soaking the ceramic block containing the iron ions in a coordination chelating agent alcohol solution in a negative pressure environment for chelation reaction so as to coordinate and chelate the iron ions in the ceramic block to form a stable chelating coordination complex; s3, filtering out the ceramic blocks, and transferring the ceramic blocks into an aqueous solution containing an adsorbent to be soaked; and S4, filtering out the soaked ceramic block, and then drying the ceramic block. The anti-discoloration solid ceramic aromatherapy block prepared by the invention can be tested for 30 days in a high-temperature environment of 50 DEG C without obvious discoloration, so that the quality of the ceramic aromatherapy block can be greatly improved, and the product competitiveness is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of vehicle-mounted aromatherapy and automobile fragrance systems, and in particular to an anti-discoloration solid ceramic block, a ceramic aromatherapy block and a preparation method thereof. Background Art

[0002] Aromatherapy is a spiritual art. The fragrance can soothe the spirit, cleanse the soul, and cultivate sentiment. Aromatherapy is also a visual art. Exquisite aromatherapy embellishes our beautiful life like a handicraft, and quality is the most important part to ensure all of this. However, the inventor found that in the process of producing in-vehicle solid ceramic aromatherapy blocks in his company, some of the fragrant ceramic blocks had serious discoloration after absorbing the essence and being stored for a period of time. The fragrance blocks changed from white to purple or brown. As car companies have higher quality requirements, they no longer accept discolored ceramic aromatherapy blocks. In order to better serve car companies and improve product competitiveness, the inventor conducted a lot of analysis, detection and testing on the causes of discoloration, and checked one by one whether it was the instability of a certain fragrance in the essence that caused the discoloration, or whether a certain fragrance reacted with calcium powder. It was finally determined that the raw material of the ceramic block, the nano-microporous calcium powder, contained some iron ions (Fe 3+ ), which will react with phenolic and aldehyde fragrances to form purple complexes, causing the product to change color to purple or brown, seriously affecting the product appearance. Similar discoloration conditions have also appeared on the market. However, the inventors of these products have ignored and evaded this issue on the grounds that discoloration is a characteristic of natural fragrances but does not affect the fragrance experience.

[0003] Solve the discoloration problem of solid ceramic aromatherapy blocks and prevent iron ions Fe 3+ It reacts with phenolic and aldehyde fragrances to form purple complexes, which greatly improves product quality, makes car fragrances more competitive, gives customers peace of mind, and avoids project cancellations due to customers not accepting the color change of fragrances. This is a difficult problem that urgently needs to be solved. Summary of the invention

[0004] In order to overcome the shortcomings and deficiencies of the prior art, the present invention provides a discoloration-resistant solid ceramic aromatherapy block, which aims to solve the problem that the ceramic aromatherapy block in the prior art solution is easy to discolor and affects the appearance of the product.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a discoloration-resistant solid ceramic block, comprising the following steps:

[0007] S1, dissolving the coordination chelating agent in alcohol to prepare a coordination chelating agent alcohol solution;

[0008] S2. Immersing the ceramic block containing iron ions in an alcohol solution of a coordination chelating agent in a negative pressure environment to perform a chelation reaction, so as to coordinate and chelate the iron ions in the ceramic block to form a stable chelated coordination complex;

[0009] S3, filtering out the ceramic blocks, and transferring them to an aqueous solution containing an adsorbent for immersion;

[0010] S4, filter out the soaked ceramic blocks and dry them to remove moisture.

[0011] Furthermore, in step S1, the weight ratio of the chelating agent to the alcohol is 1:(66-200).

[0012] Furthermore, the coordination chelating agent is at least one of citric acid, oxalic acid, lactic acid, malic acid, tartaric acid and gallic acid.

[0013] Furthermore, in step S2, the weight ratio of the ceramic block to the alcohol solution of the coordination chelating agent is (10-25):(39.6-40.6).

[0014] Furthermore, in step S2, the pressure of the negative pressure environment is 90 KPa, and the immersion time is 4 hours.

[0015] Furthermore, the adsorbent in step S3 is at least one of cation exchange resin, macroporous adsorption resin, silica gel, artificial zeolite, and activated carbon.

[0016] Furthermore, in the aqueous solution containing the adsorbent in step S3, the weight ratio of the adsorbent to the aqueous solution is (2-4):(30.4-58.2).

[0017] Furthermore, in step S3, the soaking time is 24 hours.

[0018] Furthermore, in step S4, the soaked ceramic blocks are filtered out and placed in an oven to dry out the moisture, wherein the drying temperature is 80 degrees Celsius and the drying time is 24 hours.

[0019] In a second aspect, the present invention provides a discoloration-resistant solid ceramic block prepared by the preparation method described in any one of the first aspects.

[0020] In a third aspect, the present invention provides a ceramic aromatherapy block, which is prepared by absorbing essence through the anti-discoloration solid ceramic block as described in the second aspect.

[0021] The present invention uses a coordination chelating agent alcohol solution to soak the ceramic block, wherein the alcohol solvent can dissolve the iron ions in the ceramic block, and the iron ions dissolved in the solution encounter the coordination chelating agent in the solution. Since the carboxyl group of the coordination chelating agent in the solution has electron donor properties, the electrons can be transferred to the iron ions Fe 3+Therefore, the coordination chelating agent and the iron ion can form a stable coordination compound; at the same time, because the coordination chelating agent has three -COO- coordination functional groups and a tetradentate ligand formed by a hydroxyl group, it can form multiple five-membered chelate ring stereo coordination structures with the iron ion. The five-membered ring structure chelate coordination complex has a higher stability. Therefore, the coordination chelating agent in the solution can bind the iron ion (Fe 3+ ) forms a stable chelate coordination complex through chelation, and then soaks the treated ceramic block in an aqueous solution containing an adsorbent. The trace iron ions present are adsorbed again by using an adsorbent that is selective for iron ions. Due to the acidic groups such as sulfonic acid group (-SO3H), carboxyl group (-COOH) or phenol group (-C6H4OH) contained in the adsorbent, H + Ion and iron ion Fe 3+ Ion exchange is performed to make Fe 3+ is transferred to the adsorbent, and the H + The iron ions are finally adsorbed by exchanging them with water. After drying, the treated ceramic blocks can be used to adsorb fragrances to make aromatherapy products. Without the interference of iron ions, the ceramic aromatherapy blocks will not have serious discoloration.

[0022] Compared with the existing technical solutions, the ceramic aromatherapy block of the present invention has the following advantages:

[0023] The present invention can effectively dissolve the iron ions in the ceramic block by using a coordination chelating agent alcohol solution, so that the iron ions react with the coordination chelating agent to form a stable coordination chelate, and then use an adsorbent to adsorb the existing trace iron ions, thereby removing the iron ions from the ceramic block as much as possible, thereby preventing the product from being severely discolored, greatly improving the quality of the ceramic aromatherapy block, and increasing product competitiveness. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments are described clearly and completely below. Obviously, the embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0026] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.

[0027] The raw materials involved in the present invention can be directly purchased from the market. For process parameters not specifically noted, conventional techniques can be used.

[0028] The raw materials in the examples and comparative examples of the present invention are introduced as follows:

[0029] The ceramic block of the present invention is made by the method described in Chinese invention patent CN115677334 B. In the embodiments and comparative examples of the present invention, the preparation method of the ceramic block is as follows: 81 parts of powder, 12 parts of plant fiber, 3 parts of pressing gelling agent, 2 parts of release agent, and 2 parts of deionized water are weighed by weight, stirred and mixed evenly, and pressed and formed by a press to obtain a ceramic block for use.

[0030] The powder is one or more combinations of calcium silicate, light calcium carbonate, calcium oxide and silicon dioxide.

[0031] The chelating agent is at least one of citric acid, oxalic acid, lactic acid, malic acid, tartaric acid and gallic acid.

[0032] The adsorbent is at least one of cation exchange resin, macroporous adsorption resin, silica gel, artificial zeolite and activated carbon.

[0033] Citric acid and oxalic acid were purchased from Jinan Shunyang Chemical Technology Co., Ltd.

[0034] Cation exchange resin resin purchased from Zhengzhou Xidian Power Resin Co., Ltd.

[0035] Activated carbon was purchased from Guangdong Hanyan Activated Carbon Technology Co., Ltd.

[0036] Example 1

[0037] This embodiment provides a discoloration-resistant solid ceramic block, which is made by the following method:

[0038] S1. Take 0.4 parts by weight of citric acid and add it to 39.6 parts by weight of alcohol, stir evenly to form a coordination chelating agent alcohol solution, take 20 parts by weight of a ceramic block containing iron ions and place it in the coordination chelating agent alcohol solution, soak it under a negative pressure of 90KPa for 4 hours and filter it out to coordinate and chelate the iron ions in the ceramic block to form a stable chelating complex;

[0039] S2. Add 2 parts by weight of a cation exchange resin and 1 part by weight of activated carbon to 37 parts by weight of deionized water to form an adsorption solution, place the ceramic block treated in step S1 in the adsorption solution, soak for 24 hours and filter out, and further remove trace iron ions present on the ceramic block by adsorption material;

[0040] S3. Place the ceramic block processed in step S2 in an oven to dry out the moisture on the ceramic block to obtain a discoloration-resistant solid ceramic block; wherein the baking temperature is 80 degrees Celsius and the baking time is 24 hours.

[0041] In the above, the concentration of alcohol is 95%.

[0042] Example 2

[0043] This embodiment provides a discoloration-resistant solid ceramic block, which is made by the following method:

[0044] S1. Take 0.2 parts by weight of oxalic acid and add it to 39.6 parts by weight of alcohol, stir evenly to form a chelating agent alcohol solution, take 10 parts by weight of a ceramic block containing iron ions and place it in the chelating agent alcohol solution, soak it under a negative pressure of 90 kPa for 4 hours and filter it out to coordinate and chelate the iron ions in the ceramic block to form a stable chelating complex;

[0045] S2. 1 part by weight of a cation exchange resin and 1 part by weight of activated carbon were added to 58.2 parts by weight of deionized water to form an adsorption solution, and the ceramic block treated in step S1 was placed in the adsorption solution, soaked for 24 hours and filtered out, and the trace iron ions present on the ceramic block were further adsorbed and removed by the adsorption material;

[0046] S3. Place the ceramic block processed in step S2 in an oven to dry out the moisture on the ceramic block to obtain a discoloration-resistant solid ceramic block; wherein the baking temperature is 80 degrees Celsius and the baking time is 24 hours.

[0047] In the above, the concentration of alcohol is 95%.

[0048] Example 3

[0049] This embodiment provides a discoloration-resistant solid ceramic block, which is made by the following method:

[0050] S1. Take 0.6 parts by weight of citric acid and add it to 40 parts by weight of alcohol, stir evenly to form a coordination chelating agent alcohol solution, take 25 parts by weight of a ceramic block containing iron ions and place it in the coordination chelating agent alcohol solution, soak it under a negative pressure of 90KPa for 4 hours and filter it out to coordinate and chelate the iron ions in the ceramic block to form a stable chelating coordination complex;

[0051] S2. Add 3 parts by weight of cation exchange resin and 1 part by weight of activated carbon to 30.4 parts by weight of deionized water to form an adsorption solution, place the ceramic block treated in step S1 in the adsorption solution, soak for 24 hours and filter out, and further remove trace iron ions present on the ceramic block by adsorption material;

[0052] S3. Place the ceramic block processed in step S2 in an oven to dry out the moisture on the ceramic block to obtain a discoloration-resistant solid ceramic block; wherein the baking temperature is 80 degrees Celsius and the baking time is 24 hours.

[0053] In the above, the concentration of alcohol is 95%.

[0054] Comparative Example 1

[0055] The ceramic block provided in this comparative example is made by the method described in Chinese invention patent CN115677334 B. The preparation method of the ceramic block is as follows: 81 parts of powder, 12 parts of plant fiber, 3 parts of pressing gelling agent, 2 parts of release agent, and 2 parts of deionized water are weighed by weight, mixed evenly, and pressed into shape by a press to obtain a ceramic block.

[0056] Color change time test

[0057] Take the same weight of the anti-discoloration solid ceramic block of Example 1 and the ceramic block of Comparative Example 1, adsorb flavors for 8 hours, specifically flavors containing ethyl maltol flavor, flavors containing eugenol flavor, and flavors containing salicylaldehyde flavor, and then place them in a 50 degrees Celsius environment for testing for one month to observe and record the discoloration. The results are shown in Table 1 below.

[0058] Table 1 Color change test results

[0059]

[0060] Take the same volume of the anti-discoloration ceramic block of Example 2 and the ceramic block of Comparative Example 1, adsorb flavors for 8 hours. The specific flavors are flavors containing ethyl maltol flavor, flavors containing eugenol flavor, and flavors containing salicylaldehyde flavor. Then place them in an environment of 50 degrees Celsius for testing for one month, observe and record the discoloration, and the results are shown in Table 2 below.

[0061] Table 2 Color change test results

[0062]

[0063] Take the same volume of the anti-discoloration ceramic block of Example 3 and the ceramic block of Comparative Example 1, adsorb flavors for 8 hours. The specific flavors are flavors containing ethyl maltol flavor, flavors containing eugenol flavor, and flavors containing salicylaldehyde flavor. Then place them in an environment of 50 degrees Celsius for testing for one month, observe and record the discoloration, and the results are shown in Table 3 below.

[0064] Table 3 Color change test results

[0065]

[0066] From the comparison of the above test results, it can be seen that the anti-discoloration ceramic aromatherapy block of the present invention can avoid the discoloration caused by the complexation reaction of iron ions with phenolic or aldehyde fragrances. Compared with ordinary ceramic aromatherapy blocks, the anti-discoloration solid ceramic aromatherapy block of the present invention has better color stability and aesthetics, and is therefore more competitive in the market.

[0067] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a discoloration-resistant solid ceramic block, characterized in that: The following steps are involved: S1, dissolving the coordination chelating agent in alcohol to prepare a coordination chelating agent alcohol solution; S2. Immersing the ceramic block containing iron ions in an alcohol solution of a coordination chelating agent in a negative pressure environment to perform a chelation reaction, so as to coordinate and chelate the iron ions in the ceramic block to form a stable chelated coordination complex; S3, filtering out the ceramic blocks, and transferring them to an aqueous solution containing an adsorbent for immersion; S4. Filter out the soaked ceramic blocks and dry the water.

2. The preparation method according to claim 1, characterized in that: In step S1, the weight ratio of the coordination chelating agent to the alcohol is 1:(66-200).

3. The preparation method according to claim 2, characterized in that: The coordination chelating agent is at least one of citric acid, oxalic acid, lactic acid, malic acid, tartaric acid and gallic acid.

4. The preparation method according to claim 1, characterized in that: In step S2, the weight ratio of the ceramic block to the alcohol solution of the coordination chelating agent is (10-25):(39.6-40.6).

5. The preparation method according to claim 1, characterized in that: In step S2, the pressure of the negative pressure environment is 90 KPa, and the immersion time is 4 hours.

6. The preparation method according to claim 1, characterized in that: In step S3, the adsorbent is at least one of cation exchange resin, macroporous adsorption resin, silica gel, artificial zeolite, and activated carbon.

7. The preparation method according to claim 1, characterized in that: In step S3, in the aqueous solution containing the adsorbent, the weight ratio of the adsorbent to the aqueous solution is (2-4):(30.4-58.2).

8. The preparation method according to claim 1, characterized in that: In step S3, the soaking time is 24 hours.

9. A discoloration-resistant solid ceramic block, characterized in that: The method is described in any one of claims 1 to 8.

10. A ceramic aromatherapy block, characterized in that: The anti-discoloration solid ceramic block as claimed in claim 9 is used to adsorb flavor to prepare the product.

Citation Information

Patent Citations

  • A kind of porcelain piece, ceramic incense piece and preparation method thereof

    CN115677334B